Analisa Dan Rancang Bangun Alat Pendeteksi Gangguan Fuse Cut Out Melalui Notifikasi Telegram Berbasis Global Positioning System - Hikmatul Amri; Zulkifli Zulkifli; Endang Setio Rini (Universitas Negeri Padang, 2023)
The electric power system must be able to provide a continuous supply of electrical energy with a standard amount of voltage and frequency in accordance with applicable regulations and the system must immediately return to normal conditions if the system experiences a disturbance. This tool is used to detect faults and the location of the fuse cut out (FCO). PZEM-004T sensor to read the voltage of each phase. Neo-6M GPS to get the coordinates of the location which is accessed via Google Map, then the Telegram bot sends a message to the feeder status information, the location connected to the Google Map, the transformer address and the voltage value after the disturbance. The average difference between the actual location distance to the location recorded by GPS NEO-6M is 4.10 meters and recorded by GPS Coordinates is 6.90 meters. The average percentage error of voltage values for each phase in the measuring instrument and in the sensor is in the R = 0.62 % phase, S = 8.94 % and T = 8.57 %. The Telegram bot sends a message when the FCO in the S phase is decided, namely the S Phase status is Lost, because the voltage in the S phase decreases from 221.9 V AC to 117.7 V AC, with the average duration of sending Telegram bot messages is 41.3 seconds.